Constructing Core Backbone Grid Based on the Index System of Power Grid Survivability and BBO Algorithm - Feifei Dong; Dichen Liu; Jun Wu; Fei Tang; Chunli Song; Haolei Wang; Lina Ke; Bingcheng Cen; Wentao Sun; Zhenshan Zhu (Journal of Applied Mathematics)
Constructing core backbone grid is conducive to strengthen the construction of grid structure and improve the ability of withstanding natural disasters. The survivability index of power grid is made up of four indices, namely, the resistibility, recoverability, security, and connectivity. Based on survivability, a method of constructing core backbone grid with the optimal criteria of the minimal total line length and the largest integrated survivability index is put forward. The biogeography-based optimization (BBO) algorithm is used to search for the core backbone grid. Compared with the traditional algorithms, BBO algorithm shows advantages in fast speed of convergence and high convergence precision. Moreover, the searching results for three kinds of objective functions by BBO algorithm verify the effectiveness of the proposed model of constructing core backbone grid.